Shalat Khusyu’ Menurut Tuntunan Syariat - shalat, khusyu, syari’at (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2014)
This article discusses about the nature of khusu’ prayer based on the Islamic syari’at. Most Muslims judge that a khusu’ prayer is something difficult to learn, while Quran states that one of characteristic of fiirdaus eden is a person who can do the khusu’ prayer. Shalat is an obedience which is different from another one. It was assigned to Prophet Muhammad through isra’ andmi’raj. Shalat is vertical contact between a creater and a creature. Also, it is a constraint to design a very good character. Shalat is puprosed to prevent a bad and illegal action. In order to reach the goal, however, a moslem must do shalat in a such khusu’ manner. It is impossible for a moslem to gain the goal of shalat without doing it in akhusu’ manner. On the other side, due to the lack of comprehension on khusu’ prayer, many people conduct a training of khusu’ prayer as if it is based on the sunnah.Naturallay, the meaning of khusu’ prayer has broader scope compared to what clarified in the training it self.